ESTIMATION OF ARSENIC(III) IN ORGANIC ARSINES AND ITS COMPLEXES USING POTASSIUM BROMATE AND POTASSIUM IODATE AS OXIDANTS - Anu Sharma; Gaurav Sharma; Mu Naushad; Deepak Pathania (Journal of the Chilean Chemical Society, 2016)
Oxidimetric quantitative determination of arsenic(III) in organic arsines and their complexes with tin(IV) and mercury(II) has been attempted visually, potentiometrically and conductometrically. In each method, standard potassium bromate and potassium iodate oxidants were used in absolute alcohol medium. In these methods, known weight of organic arsines was dissolved in a mixture of absolute alcohol and concentrated hydrochloric acid. The resulting solution was titrated with standard potassium bromate/iodate solutions as oxidants using CCl4 as indicator in visual method. In case of conductometric and potentiometric titrations using potassium iodate/bromated, the results obtained were comparable to visual method. The percentage of arsenic for 1/10 mol L-1 KIO3 and 1/10 mol L-1 KBrO3 were found to be 11.73% and 11.71%, respectively. It led to the authenticity of the results obtained by visual method. 10 mg to 20 mg of the compound under test gave the results within the standard deviation error. The estimation of arsenic (III) was achieved within half an hour.